ANALISIS PENGARUH LABEL HALAL, BRAND IMAGE DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN IMPOR : STUDI PADA KONSUMEN MUSLIM URBAN DI KOTA CIKARANG - Lisa Permatasari; Muhamad Syahwildan (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the effect of halal label, brand image, and electronic word of mouth (E-WOM) on purchasing decisions for imported food products for urban Muslim consumers in Cikarang City. The study used a quantitative approach with purposive sampling technique, involving 30 respondents. Data were collected through online questionnaires and analyzed using multiple linear regression. The results showed that: (1) Halal label partially has no significant effect on purchasing decisions, (2) Brand image partially has no significant effect on purchasing decisions, (3) E-WOM partially has a significant effect on purchasing decisions, and (4) Halal label, brand image, and E-WOM simultaneously have a significant effect on purchasing decisions with a contribution of 78.7%.